Solar light harvesting nanomaterial (BaZrS3) for photocatalytic activity and OER reaction. (January 2023) - Yasmin, Nazia; Safdar, Muhammad; Ali, Ghulam; Khan, Hasan M.; Mirza, Misbah
Abstract: The trend to use highly efficient and low cost multinary metal chalcogenides (MMCs) in the field of electrochemical and photocatalytic degradation of dyes increases day by day due to their narrow band gaps. Herein, BaZrS3 (BZS) nanomaterial is synthesized via hydrothermal route. XRD spectra with TEM and EDX results reveal that synthesized nanomaterial is well crystallized with single phase orthorhombic structure. UV–visible spectroscopy reveals its optical properties. Band gap of synthesized nanomaterial is 2.3 eV. Electrocatalytic oxygen evolution reaction (OER) and photocatalytic activity of prepared BZS has been studied by degrading the textile dye Congo red (CR) under direct sunlight. The electrochemical studies for OER reveal low value of overpotential of 312 mV with small Tafel slope (60mV/dec) at current density of 10 mA/cm 2 . Our synthesized material also shows high stability towards OER. The removal of CR by BZS after adsorption-desorption equilibrium is 70.96%. CR dye was adsorbed onto the surface of BaZrS3 and its adsorption phenomenon is related to its high specific surface area. The degradation efficiencies of 50 ppm, 60 ppm, 70 ppm and 100 ppm CR solutions are 95.34%, 92.47%, 87.80%, 70.43% in 30 min under solar irradiation, respectively. Graphical abstract: Herein, the BZS nanomaterial is synthesized via hydrothermal route. The Band gap of synthesized nanomaterial is 2.3 eV. The electrochemical studies for OER reveal low value of overpotential of 312 mV with small Tafel slope. For 50 ppm, 60 ppm, 70 ppm and 100 ppm removal efficiencies under adsorption-desorption equilibrium for 1 h are 70.96%, 69.43%, 67.21% and 60% and further increased to 95.34%, 92.47%, 87.80%, 70.43% in 30 min of solar irradiation, respectively. Image 1 Highlights: Hydrothermal technique is used to fabricate BaZrS3 (BZS) MMCs with crystalline size 6 nm. Nanomaterial possess narrow band gap i.e. 2.3 eV. Synthesized nanomaterial has Specific surface area (SSA) 236.40 m 2 /g. The electrochemical studies for OER reveal low value of overpotential of 312 mV with small Tafel slope (60mV/dec) at 10 mA/cm 2 current density. Removal efficiencies of CR for 50 ppm, 60 ppm, 70 ppm and 100 ppm reaches to 95.34%, 92.47%, 87.80%, 70.43% respectively.